Membrane-wall interrelationship in Gaffkya homari: sulfhydryl sensitivity and heat lability of nascent peptidoglycan incorporation into walls. - Neuhaus, F C (1980)
Membrane-walls from Gaffkya homari require a specific interrelationship between membrane and wall that functions in the incorporation of nascent peptidoglycan into the preexisting peptidoglycan of the wall. Two different methods were used to inhibit selectively this incorporation process: (i) sensitivity to sulfhydryl reagents and (ii) heat inactivation. Of the sulfhydryl reagents tested, 2.2 mM iodoacetamide inhibited the synthesis of wall peptidoglycan 50%, whereas greater than 100 mM was required to inhibit the synthesis of sodium dodecyl sulfate (SDS)-soluble peptidoglycan. Heat treatment at 37 degrees C (t 1/2 = 5.7 min) inhibited wall peptidoglycan synthesis without affecting SDS-soluble peptidoglycan synthesis. Inhibition of LD-carboxypeptidase by iodoacetamide and heat gave 50% inhibition and t 1/2 values similar to those observed for the incorporation process. Thus, it is suggested that the LD-carboxypeptidase may be one of the enzymes responsible for the sulfhydryl sensitivity and heat lability and that this enzyme may play a role in the relationship between membrane and wall in G. homari.